Unraveling Consumer Behavior Dynamics in Beverage Marketing: Mengungkap Dinamika Perilaku Konsumen dalam Pemasaran Minuman - Lailah, Nur; Kumala Sari, Herlinda Maya (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how packaging, promotion, and brand image influence consumer purchasing decisions, focusing on Le Minerale, a key player in the beverage industry. With Le Minerale's Top Brand Index facing a downward trend, maintaining competitiveness is challenging. Employing a quantitative approach with descriptive methods, we surveyed 100 respondents using online questionnaires in Sidoarjo City. Utilizing the Likert scale and multiple linear regression analysis, our findings reveal that packaging significantly impacts purchasing decisions, followed by promotion and brand image. These results underscore the importance of strategic marketing efforts to enhance packaging design and promotional activities, providing valuable insights for marketers aiming to bolster brand performance and competitiveness. Highlight: Consumer Influence: Study on packaging, promotion, and brand image's impact. Marketing Strategy: Insights for effective marketing strategies and brand performance. Competitive Edge: Enhancing beverage industry's competitiveness through consumer behavior analysis. Keywoard: Consumer behavior, Marketing, Brand image, Beverage industry, Competitive advantage.